GLHOVE: A framework for uniform coverage monitoring using cluster-tree wireless sensor networks - Felske, Mitchel S.; Montez, Carlos; Pinto, Alex S. R. [UNESP]; Vasques, Francisco; Portugal, Paulo (Institute of Electrical and Electronics Engineers (IEEE), 2013)
In several monitoring applications, such as those that can be found in industrial factory floor, it may be necessary to obtain an uniform sensing coverage, providing as much as possible the same coverage degree for the entire network area. The IEEE 802.15.4 has become an important standard in wireless sensor networks. However, the use of cluster-tree topology in these networks hampers a fair and uniform coverage in the sensing area. Clusters more distant from the base station are eventually adversely affected, with messages from its sensors delayed and discarded. In this paper, we propose a framework, entitled GLHOVE, whose goal is to make a trade-off between a minimum and uniform coverage area and the energy consumption of the network. The simulation results show an increase up to 20% of the fairness metric (w.r.t. messages received by base station). © 2013 IEEE.